Normal walking support mechanical orthosis with rotation induction to lower leg for patients with knee osteoarthritis - Taku ITAMI; Ken’ichi YANO; Ichidai MORI; Kazuhiro KAMEDA; Takaaki AOKI; Toshitsugu KISHIDA; Norio HAYASHI; Naruki MATSUI; Masanori SUGAWARA; Nobuyuki SHINODA (Nihon Kikai Gakkai ronbunshu, 2019)
Knee osteoarthritis(Knee-OA) is a disease caused by age-related muscle weakness, obesity, or sport injury, and it has been estimated that approximately one in two people may experience it by the age of 85. Most cases of knee-OA lead to a gait problem due to pain during walking, with the result that knee-OA is a significant cause of reduced personal quality of life (QOL). One of the characteristics of knee-OA who are classified as grade II to III of Kellgren-Lawrence classification is rotation dyskinesia of the knee joint due to the degeneration of the system around the knee. This rotation movement is crucial for impact absorption, balanced walking and stabilization of the knee joint and this movement is one of key elements in walking. In the present study, we focused on the rotation of the lower leg relative to the movement of the ankle joint during walking stance phase, and we developed a mechanical orthosis of the new type of ankle-foot orthosis (AFO), which induces rotation of the lower leg in conjunction with the movement of the ankle joint mechanically. The mechanical induction of rotation movement is used the movement difference due to the angle change of inside and outside bars in conjunction with ankle angle. We verified the effectiveness of the developed orthosis by measuring the amount of rotation, lateral thrust, Womac test while five subjects with knee osteoarthritis. Based on the results, the effectiveness of our developed orthosis was confirmed.